If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + -34 = 49 Reorder the terms: -34 + w = 49 Solving -34 + w = 49 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '34' to each side of the equation. -34 + 34 + w = 49 + 34 Combine like terms: -34 + 34 = 0 0 + w = 49 + 34 w = 49 + 34 Combine like terms: 49 + 34 = 83 w = 83 Simplifying w = 83
| 6x+3-4x=-7 | | k/9-9=10 | | 0=4x^2+3x-10 | | 2x=2g | | -79=3x+7x+1 | | 0=-d^2+d+12 | | 2x-6-5x=6 | | 1-1-1-1-1-1-1-1-1-1-1-1-1-1-1x-2x-3-456g-a=g | | 5x-6-3x=4 | | 5x-5-6x=-6 | | 9x=8x-8 | | 2x+2x=3x+5x+1-5 | | 4-3x+5(2-x)=6(x+9) | | 5x+2-2x=8 | | 9n^2+16=-24n | | 5+5x=-50 | | 5x+-2-2x=8 | | 6(2x-1)-12=7+12(x+1) | | -0.875-(-n)=-0.583 | | m+6m+5m+8= | | 9=-5p+5+6p | | 4(2x+5)-18=36 | | -3=9p-9-8p | | (8)(16)=(6)(2x+6) | | 4=3p+6-2p | | -9x=-10x | | -3=-5p+9+6p | | 1-0.7k=1 | | -9=7p-15-6p | | 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p |